2015
DOI: 10.1136/bmjopen-2015-009006
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of anti-VEGF injections in the Portuguese National Health System

Abstract: ObjectivesTo analyse the temporal and geographical diffusion of antivascular endothelial growth factor (anti-VEGF) interventions, and its determinants in a National Health System (NHS).SettingNHS Portuguese hospitals.ParticipantsAll inpatient and day cases related to eye diseases at all Portuguese public hospitals for the period 2002–2012 were selected on the basis of four International Classification of Diseases 9th revision, Clinical Modification (ICD-9-CM) codes for procedures: 1474, 1475, 1479 and 149.Prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Restrictions in healthcare systems may, in part, account for some of the variation in outcomes observed between countries. Access to ophthalmology facilities may also be an issue in some countries (Marques et al 2015). This also highlights that any differences in the number of patients enrolled between different clinics and countries could introduce bias in the current study.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Restrictions in healthcare systems may, in part, account for some of the variation in outcomes observed between countries. Access to ophthalmology facilities may also be an issue in some countries (Marques et al 2015). This also highlights that any differences in the number of patients enrolled between different clinics and countries could introduce bias in the current study.…”
Section: Discussionmentioning
confidence: 91%
“…It was also difficult to determine associations between number of injections and VA outcomes in subgroups due to small patient numbers, and the study was not designed to assess these in detail. Access to ophthalmology facilities may also be an issue in some countries (Marques et al 2015). in response to outcomes), and achievement of short-term gains may result in reduction of future injections despite the possibility of further improvement; this was evidenced in POLARIS (Table 4), which indicates that outcomes seem to drive injections e947 as much as injections drive outcomes when using as-needed regimens in DME.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patient management and access to health care may have differed between study sites, resulting in differences in preventive and treatment options. 50 , 51 …”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have showed that anti-VEGF intravitreal injections prevented vision loss in the majority of patients and, in some cases, significantly improved vision 2 3 5. The positive impact of anti-VEGF injections in visual outcomes2 6–8 combined with the lack of previous efficient treatments, led to rapid diffusion of anti-VEGF treatments in many countries 4 6 9 10…”
Section: Introductionmentioning
confidence: 99%